2023
DOI: 10.1017/s0958344023000125
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of social virtual reality for virtual exchange

Abstract: Mentored online intercultural interaction offers foreign language learners the opportunity to develop different competences, including intercultural, linguistic, and digital competence (O’Dowd, 2021). Such virtual exchange (VE) projects typically involve computer-mediated communication via, for example, Zoom. However, the use of high-immersion virtual reality (VR) for synchronous online collaboration in VE projects has received little attention. This study investigated the effect of VR on students’ levels of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…High‐immersion VR is an increasingly valued environment for language learners. Unsurprisingly, language scholars have investigated the potential of VR for facilitating virtual exchanges (Gruber et al, 2023; Jauregi‐Ondarra et al, 2021), social interaction (Gruber & Kaplan‐Rakowski, 2022; Li & Lan, 2021; Thrasher, 2023), pragmatics (Taguchi, 2021), vocabulary learning (Alfadil, 2020; Papin & Kaplan‐Rakowski, 2022) and one‐on‐one tutoring (Kaplan‐Rakowski & Gruber, 2021). Practicing various language skills in VR has also received attention, such as writing (Lan & Tam, 2022), speaking (Gruber & Kaplan‐Rakowski, 2020; Kaplan‐Rakowski & Gruber, 2023; Thrasher, 2022, 2023), and listening (Peixoto et al, 2019; Ye & Kaplan‐Rakowski, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…High‐immersion VR is an increasingly valued environment for language learners. Unsurprisingly, language scholars have investigated the potential of VR for facilitating virtual exchanges (Gruber et al, 2023; Jauregi‐Ondarra et al, 2021), social interaction (Gruber & Kaplan‐Rakowski, 2022; Li & Lan, 2021; Thrasher, 2023), pragmatics (Taguchi, 2021), vocabulary learning (Alfadil, 2020; Papin & Kaplan‐Rakowski, 2022) and one‐on‐one tutoring (Kaplan‐Rakowski & Gruber, 2021). Practicing various language skills in VR has also received attention, such as writing (Lan & Tam, 2022), speaking (Gruber & Kaplan‐Rakowski, 2020; Kaplan‐Rakowski & Gruber, 2023; Thrasher, 2022, 2023), and listening (Peixoto et al, 2019; Ye & Kaplan‐Rakowski, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…VR also offers a significant advantage in terms of boosting student engagement. Previous research, including the work of Gruber et al (2023), has shown that VR can be particularly beneficial in this regard. By immersing learners in a virtual environment, VR headsets can effectively eliminate distractions and enable them to concentrate fully on their learning tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially relevant in cultural education, as learners must observe the surroundings and cultural objects that are presented in close proximity within a virtual environment. Gruber et al (2023) have found a compelling link between favorable attitudes toward interactive learning environments and enhanced communication among students. This underscores the significance of establishing a vibrant and stimulating learning atmosphere that promotes open communication and teamwork.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations